Comorbidity and health care visit burden in working-age commercially insured patients with diabetic macular edema - Kiss S (Dove Medical Press, 2016)
Szilárd Kiss,1 Hitesh S Chandwani,2 Ashley L Cole,2 Vaishali D Patel,2 Orsolya E Lunacsek,3 Pravin U Dugel4 1Department of Ophthalmology, Weill Cornell Medical College, New York, NY, 2Global Health Economics and Outcomes Research, Allergan, Inc., Irvine, CA, 3Global Health Economics and Outcomes Research, Xcenda, LLC, Palm Harbor, FL, 4Retinal Consultants of Arizona and USC Eye Institute, Phoenix, AZ, USA Purpose: To examine the comorbidity profile and update estimates of health care resource utilization for commercially insured, working-age adults with diabetic macular edema (DME) relative to a matched comparison group of diabetic adults without DME. Additional comparisons were made in the subgroup of pseudophakic patients. Patients and methods: A retrospective matched-cohort study of commercially insured diabetic adults aged 18–63 years was conducted using medical and outpatient pharmacy claims (July 1, 2008–June 30, 2013). Outcomes included diabetes-related and ocular comorbidities and health care resource utilization (any health care visit days, outpatient visit days, inpatient visit days, emergency room visits, eye care-related visit days, unique medications) in the 12-month post-index period. Results: All diabetes-related and ocular comorbidities were significantly more prevalent in DME cases versus non-DME controls (P<0.05). A significantly greater proportion of DME cases utilized eye care-related visits compared with non-DME controls (P<0.001). DME cases had almost twice the mean number of total health care visit days compared to non-DME controls (28.6 vs 16.9 days, P<0.001), with a minority of visit days being eye care-related (mean 5.1 vs 1.5 days, P<0.001). Similar trends were observed in pseudophakic cohorts. Conclusion: This working-age DME population experienced a mean of 29 health care visit days per year. Eye care-related visit days were a minority of the overall visit burden (mean 5 days) emphasizing the trade-offs DME patients face between managing DME and their overall diabetic disease. Insights into the complex comorbidity profile and health care needs of diabetic patients with DME will better inform treatment decisions and help optimize disease management. Keywords: health care resource utilization, diabetes, real-world evidence, pseudophakic, retinal disease